CLASSIFICATION OF POOR ASSISTANCE RECIPIENTS AT THE VILLAGE BALANCE OFFICE - April Liza Anzani Manurung; Hambali Hambali; Zulfan Efendi (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: The poor community is a condition in which the community does not have adequate facilities and infrastructure and an adequate environment, with the quality of housing and settlements far below the eligibility standard and uncertain livelihoods covering all multidimensional dimensions. The Pasiran Village Office, Sei Dadap District, is one of the agencies located in the Pasiran area, Sei Kamah. Where the Pasiran Village Hall Office carries out activities to distribute assistance to village communities who are declared to be underprivileged or have low incomes below 3.5 million. With such a large number of village people, an in-depth analysis is needed to determine which poor people are entitled to receive Non-Cash Food Assistance from the government. The solution to this problem is to use data mining with the Naïve Bayes algorithm for data classification. Data mining is the science of extracting information by utilizing data sets to obtain valuable information with a large enough data size through the process of extracting data or filtering data. The classification application uses the naïve Bayes algorithm used at the Pasiran Village Office to produce a classification of beneficiaries, namely Worthy and Unworthy based on the attributes of Citizenship, Family Group, ASN Status, and Having a Healthy Family Card.            Keywords: data mining; naïve bayes; classification, beneficiary  Abstrak: Masyarakat miskin merupakan suatu kondisi dimana keadaan masyarakat yang tidak memiliki sarana dan prasarana serta lingkungan yang memadai, dengan kualitas perumahan dan pemukiman yang jauh dibawah standar kelayakan serta mata pencaharian yang tidak menentu yang mencakup seluruh multidimensi. Kantor Balai Desa Pasiran Kecamatan Sei Dadap merupakan salah satu instansi yang berada di daerah Pasiran, Sei Kamah. Dimana Kantor Balai Desa Pasiran melakukan kegiatan pembagian bantuan terhadap masyarakat desa yang dinyatakan kurang mampu atau memiliki penghasilan rendah dibawah 3,5 juta. Dengan jumlah masyarakat desa yang begitu banyak, diperlukan analisis yang mendalam untuk menentukan masyarakat tidak mampu yang berhak untuk mendapatkan Bantuan Pangan Non Tunai dari pemerintah. Solusi dari permasalahan tersebut adalah menggunakan data mining dengan algoritma naïve bayes untuk klasifikasi data. Data mining merupakan suatu ilmu untuk menggali informasi dengan memanfaatkan kumpulan data untuk mendapatkan berbagai informasi yang berharga dengan ukuran data yang cukup besar melalui proses penggalian data atau penyaringan data. Aplikasi klasifikasi menggunakan algoritma naïve bayes yang terapkan pada Kantor Balai Desa Pasiran menghasilkan klasifikasi warga penerima bantuan yaitu Layak dan Tidak Layak berdasarkan atribut Kewarganegaraan, Golongan Keluarga, Status ASN dan Memiliki Kartu Keluarga Sehat. Kata kunci: data mining; naïve bayes; klasifikasi, penerima bantuan